2016
DOI: 10.1177/0954411916637383
|View full text |Cite
|
Sign up to set email alerts
|

Effect of posterior decompression extent on biomechanical parameters of the spinal cord in cervical ossification of the posterior longitudinal ligament

Abstract: Ossification of the posterior longitudinal ligament is a common cause of the cervical myelopathy due to compression of the spinal cord. Patients with ossification of the posterior longitudinal ligament usually require the decompression surgery, and there is a need to better understand the optimal surgical extent with which sufficient decompression without excessive posterior shifting can be achieved. However, few quantitative studies have clarified this optimal extent for decompression of cervical ossification… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
22
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 13 publications
(25 citation statements)
references
References 48 publications
2
22
1
Order By: Relevance
“…Kim et al and Khuyagbaatar et al also reported von Mises stresses of 0 -400 kPa at similar compression ratios. 83,106 This is higher than the stresses we reported, but again, at a much higher amount of compression.…”
Section: Discussioncontrasting
confidence: 66%
See 2 more Smart Citations
“…Kim et al and Khuyagbaatar et al also reported von Mises stresses of 0 -400 kPa at similar compression ratios. 83,106 This is higher than the stresses we reported, but again, at a much higher amount of compression.…”
Section: Discussioncontrasting
confidence: 66%
“…86 It is interesting that all these FE models report similar strain levels even though There are FE models which address the effects of cervical myelopathy. 79,82,83,106,108 However, the majority of these, as previously mentioned, have simplified boundary conditions. Khuyagbaatar et al is the first group to incorporate comprehensive spinal canal anatomy with the spinal cord to investigate cord compression caused by the ossified posterior longitudinal ligament.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Posterior laminectomy with wide opening of the foraminal space would be favorable in this particular case, allowing decompression away from the offending pathology including osteophytes, ligaments, and discs. This would, however, require fusion which is usually achieved through posterior LMS fixation systems[ 29 ] [ Table 1 ].…”
Section: Discussionmentioning
confidence: 99%
“…14,[25][26][27][28] In our previous study, an FE model of the cervical spine with the spinal cord, including white matter, gray matter, dura mater with nerve roots, denticulate ligaments, and cerebrospinal fluid (CSF), was developed and investigated the effect of surgical extents in three different decompression methods on changes in stress, strain, and posterior shift of the spinal cord for cervical OPLL. 29 However, few studies have focused on predicting stresses and strains in the spinal cord with the cervical OPLL under different neck positions before and after surgical intervention. In this study, the biomechanical parameters (von-Mises stress, maximum principal strain, and CSA) in the spinal cord under the flexion, neutral, and extension positions in cervical OPLL were then investigated for pre-operative and laminectomy models of the cervical spine, using the previously developed FE model of the cervical spine with the spinal cord.…”
Section: Introductionmentioning
confidence: 99%